Optimalisasi Soft Skill Pada Lembaga Pendidikan Di Era 4.0 - Irawan, Andri; Setiawati, Tia; Andiana, Anisa (Green Publisher Indonesia, 2023)
The purpose of this research is to examine and describe the results of research on Soft Skills in Indonesia, especially in the scope of educational institutions. From these findings, it is used as a basis for finding new ways, especially to optimize Soft Skills in Educational Institutions. The research method uses content analysis of articles from 2015-2022 from the Google Schoolar, Scopus.com and Garuda sites which are searched using the keyword